THE RELATIONSHIP OF SEA SURFACE AND CHLOROFILE-ON THE FISH TUNA MADIDIHANG (Thunnus albacares) FISHING USING AQUA MODIS SATELLITE IMAGE IN INDIAN OCEAN - Praja Kusuma Andita; Alit Hindri Yani; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The study aims to see the distribution of tuna fish yellowfin tuna (Thunnus albacares) in the Indian Ocean Section West, see CPUE tuna yellowfin tuna (Thunnus albacares), variability of chlorophyll-a and the temperature of the sea surface every month and season as well as a correlation to chlorophyll-a and the surface temperature sea against the distribution of yellowfin tuna (Thunnus albacares) in 2013 using AQUA MODIS satellite imagery. The processed data is the data the fishing logbook in 2013 of PPS Bungus with longline fishing gear, the data of chlorophyll-a and ocean surface temperature obtained from the site ERDDAP, data analysis used is the analysis of the density which draws on research Riolo (2006). From the results of this study found that the variability of chlorophyll-a in the waters of the Western Indian Ocean was highest in November amounting to 17.144 mgm-3 / month, the value of the highest sea surface temperature variability occurs in May is 34.31 ° C and for the value of CPUE the highest occurred in June with a value from 16.667 to 10,989 head / 1000 hook / pixel area, with the number of the hook as much as in 2124 the catch hook with an average of 3.0683 tailKeywords: AQUA MODIS, CPUE, Chlorophyll-a, Sea surface temperature, Tuna Madidihang